ANALISIS PENJADWALAN PEKERJAAN SALURAN DRAINASE JALAN LINTAS SELATAN LOT.6 KABUPATEN TULUNGAGUNG DENGAN METODE PERT - Ade Irfan Taranau; Hanie Teki Tjendani (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The construction of the South Cross Road Lot.6 in Tulungagung Regency is still in progress with an initial contract value of Rp. 518,708,635,957. - not including VAT. The construction of this road starts from Karanggongso – Nglarap (Trenggalek Regency) for 10,450 km and Nglarap – Klatak (Tulungagung Regency) for 4,414 km. Construction of Drainage channels in the South Cross Road construction project Lot.6 district. Tulungagung is very diverse, ranging from V-ditch and U-ditch work. Due to the complexity of the activities that must be carried out in a construction project, supporting equipment is needed that can speed up data processing quickly, accurately and precisely. The equipment is a computer and its software, one of which uses the Microsoft Project program. For the drainage channel construction project itself, it has a budget plan of Rp. 46,179,268,645.48 with a planned completion of 763 days. The data collection carried out in this study was secondary data from the South Cross Road project Lot.6 Tulungagung Regency in the form of a Budget Plan, Time Schedule, project data and shop drawings. Evaluation is carried out by analyzing the duration of each activity in the drainage canal work and dependency logic based on the PDM analysis in Microsoft Project then analyzing three-time estimates based on the PERT method and analyzing the cost of the project plan based on the PERT analysis. From the evaluation results it was found that the analysis using the PERT method was more efficient with work acceleration of 4 working days with a duration of 759 days, while the costs for this project were in accordance with the plan, because there were no additional resources and materials in the implementation of the project. Based on the critical path analysis in the Microsoft Project, the critical path work is excavation work for drainage channels and also mortar stone work, so that the completion of this project is very dependent on these two works